Characterization of cocaine-induced block of cardiac sodium channels. - Crumb, W J (1990)
Recent evidence suggests that cocaine can produce marked cardiac arrhythmias and sudden death. A possible mechanism for this effect is slowing of impulse conduction due to block of cardiac Na channels. We therefore investigated its effects on Na channels in isolated guinea pig ventricular myocytes using the whole-cell variant of the patch clamp technique. Cocaine (10-50 microM) was found to reduce Na current in a use-dependent manner. The time course for block development and recovery were characterized. At 30 microM cocaine, two phases of block development were defined: a rapid phase (tau = 5.7 +/- 4.9 ms) and a slower phase (tau = 2.3 +/- 0.7 s). Recovery from block at -140 mV was also defined by two phases: (tau f = 136 +/- 61 ms, tau s = 8.5 +/- 1.7 s) (n = 6). To further clarify the molecular mechanisms of cocaine action on cardiac Na channels, we characterized its effects using the guarded receptor model, obtaining estimated Kd values of 328, 19, and 8 microM for channels predominantly in the rested, activated, and inactivated states. These data indicate that cocaine can block cardiac Na channels in a use-dependent manner and provides a possible cellular explanation for its cardiotoxic effects.